Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA): Case report - Utama, Bobby Indra; Reinaldo, Poldo; Sari, Puspita (Andalas Obstetrics And Gynecology Journal, 2022)
Background: Hemivaginal obstruction syndrome and ipsilateral renal anomalies are known as Herlyn-Werner-Wunderlich syndrome (HWWs) or better known by the acronym OHVIRA (Obstructed Hemivagina and Ipsilasteral Renal Anomaly). It occurs as a result of complete failure of the MÃ¼llerian ducts to fuse and accounts for about 5% of MÃ¼llerian duct anomalies. Initial manifestations usually appear as a result of secretions accumulating within the hemivaginal obstruction. Patients with HWWs can come with complaints of lower abdominal pain, severe dysmenorrhea, pelvic or vaginal mass, abnormal vaginal discharge, acute urinary retention, fever or vomiting. Therefore, careful diagnosis and appropriate management of this condition is desirable. The objective of the study was to report on the management of the obstruction due to HWWs. Case Report: A 12-year-old patient was admitted to the gynecology ward of Dr. M. Djamil Central General Hospital from polyclinic with abdominal pain since 4 months before being admitted to the hospital. The pain gets worse every day before menstruation and decreases when given painkillers. Bleeding from the vagina often recurs with blackish color, a little smelly since the 1 month ago. Conclusion: OHVIRA syndrome is a triad characterized by hemivaginal obstruction and agenesis of the ipsilateral kidney (OHVIRA) and uterus in the delphys. Clinical symptoms in general are cyclic dysmenorrhea, palpable mass due to accumulation of menstrual flow, and severe pelvic pain which can later develop into a persistent form as a result of prolonged retention of menstrual secretions, obstructed hemivagina. Management options are surgical resection of the obstructed vaginal septum and drainage.